ACTIVITIES OF ASCORBIC PEROXIDASE (Apx) And TANNIN CLONES PB 260 ON TAPPING PANEL DRYNESS (TPD) - ADE FIPRIANI LUBIS; ROSMAYATI; RADITE TISTAMA; REVANDY I.M DAMANIK (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2021)
TPD was a physiological caused by overstimulation ethylene an overproduction of reactive oxygen species (ROS). As an adaptive response, plant produce antioxidant such as secondary metabolites one of them was ascorbic acid (AsA). Exogenous application of AsA has been very effective in improving plant growth and development by altering oxidative defense system and induction of tannin synthesis in response to environmental stresses may also indicate potential functions. These Research aimed to provided activity of ascorbic peroxidase, tannin and production in Hevea brasiliensis Clones PB 260 affected Tapping Panel Dryness and to find the effect of ascorbic acid on production latex in in Hevea brasiliensis Clones PB. The research was conducted in rubber plantation of Sungei Putih Research Institute, Deli Serdang Regency North Sumatra with PB 260 as clone were planted in 2006 to 2007 at ± 54 m above sea level. The interval for treatment was once a week for 4 months. The observation was made 4th months after first application. The parameters observed were production, the activity of Askorbic peroxidase and tanin. The result showed Applicated ascorbic acid 150 ppm can increased the production of latex and tannins in rubber plants that are exposed to tapping panel dryness (TPD) but reduced the activity of the ascorbate peroxidase (Apx).